(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe anthropometric characteristics and BMI classification among first-year students at Vietnam National University, Hanoi and to compare BMI classification according to age group, sex, and school affiliation. Methods: A cross-sectional study was conducted using routine health examination data collected from first-year students at the beginning of the academic year. Height and weight were measured by healthcare staff, and BMI was calculated and classified according to Asian BMI criteria. Descriptive statistics and chi-square tests were used for data analysis. Results: A total of 16,320 students were included in the study. The mean BMI was 21.03 ± 3.48 kg/m². Normal BMI accounted for 52.4% of students, while 23.4% were underweight, 11.8% were overweight, and 12.4% were obese. Significant differences in BMI classification were observed according to sex, age group, and school affiliation (all p < 0.05). Male students had higher proportions of overweight and obesity, whereas female students showed higher proportions of underweight. Conclusion: Both undernutrition and excess body weight were common among first-year university students. Nutritional status differed significantly according to demographic and academic characteristics, highlighting the importance of early health screening and nutrition promotion programs for university students.